A rare case of disseminated tuberculosis; multiple intracranial and intramedullary tuberculomas with concurrent tuberculous spondylitis and meningitis. (August 2020) - Rezaee, Hamid; Tavallaii, Amin; Keykhosravi, Ehsan; Nazeminezhad, Ramin; Asghari, Raana; Alenabi, Anita
Abstract: Concomitant presentation of intracranial and intramedullary tuberculomas is a rare entity. We report a 38-year-old immunocompetent woman with intramedullary and intracranial tuberculomas with concurrent tuberculous spondylitis and meningitis, who presented with paraparesis and back pain. Despite initial antituberculous therapy, the patient's neurologic status deteriorated with the development of paraplegia. Following surgical intervention, the patient gradually recovered muscle strength and bladder function.